Standarisasi Simplisia Daun Ekor Kucing (Acalypha hispida Burm.f.) dari Tiga Daerah Berbeda - Bay, Wilhelmina Walu; Hermanu, Liliek S.; Sinansari, Restry (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2020)
The fox tail (Acalypha hispida) is known for its many benefits and has been used in traditional medicine. This aim of this research was determining the profile of specific and non specific standardization of fox tail leaves from three different areas (Batu, Bogor and West Sumba). The specific parameters consist of identity, organoleptic, microscopic, water soluble extract, ethanol soluble extract, phytochemical screening, chromatogram profile determination by thin layer chromatography (TLC), determination of infrared spectrum profile (IR), determination of UV spectrum profile and determination of secondary metabolite content (phenol and flavonoid). Non spesific parameters include shrinkage drying, ash content, acid insoluble ash, water soluble ash, percent foreign material and pH measurement. The result of standardization of dried powder fox tail leaves, have value of soluble ethanol extract ˃ 14%, water soluble extract ˃ 23%, contain flavonoids compounds, polyphenols, tannins, quinones and triterpenoids, total flavonoid levels > 0.2% and phenol > 0.7%, pectrophotometry IR result showed the presence of O-H, C-H, C = C and C-C groups, total ash content < 15.5%, acid insoluble ash < 2.5%, water soluble ash < 5.5%, drying shrinkage level < 10% and pH 4.5-5.